Productivity of three sub-types of Sudan desert sheep at El Huda research station, Sudan - Suleiman, A.H.; Wilson, R.T. (International Livestock Centre for Africa, 1989)
Shugor, Dubasi and Watish sub-types of Sudan Desert sheep were evaluated on the basis of 3 productivity indices (weight of lamb weaned/ ewe/yr, weight weaned/kg ewe/yr and weight weaned/kg 0.75/ewe/yr). Components used to construct the indices were litter weight at 120 d, parturition interval, survival to 120 d and ewe postpartum weight. There were differences among sub-types in all components but, because of interactions among them, there were no differences in the indices. The indices were 16.8 kg, 419 g and 1.14 kg and were lower than those found in other studies. Suggestions for improving productivity are made.